Rats bred for low and high running capacity display alterations in peripheral tissues and nerves relevant to neuropathy and pain. Issue 10 (6th September 2017) - Cooper, Michael A.; Jack, Megan M.; Ryals, Janelle M.; Hayley, Page; Escher, Taylor; Koch, Lauren G.; Britton, Steven L.; Raupp, Shelby M.; Winter, Michelle K.; McCarson, Kenneth E.; Geiger, Paige C.; Thyfault, John P.; et al.
Abstract: Introduction: Diet and activity are recognized as modulators of nervous system disease, including pain. Studies of exercise consistently reveal a benefit on pain. This study focused on female rats to understand differences related to metabolic status and peripheral nerve function in females. Methods: Here, we investigated parameters of peripheral nerve function relevant to pain in rats selectively bred for high (high‐capacity runners; HCR) or low endurance exercise capacity (low‐capacity runners; LCR) resulting in divergent intrinsic aerobic capacities and susceptibility for metabolic conditions. Results: LCR female rats have reduced mechanical sensitivity, higher intraepidermal nerve fiber density and TrkA‐positive epidermal axons, increased numbers of Langerhans and mast cells in cutaneous tissues, and a higher fat content despite similar overall body weights compared to female HCR rats. Sensory and motor nerve conduction velocities, thermal sensitivity, and mRNA expression of selected genes relevant to peripheral sensation were not different. Conclusions: These results suggest that aerobic capacity and metabolic status influence sensory sensitivity and aspects of inflammation in peripheral tissues that could lead to poor responses to tissue damage and painful stimuli. The LCR and HCR rats should prove useful as models to assess how the metabolic status impacts pain. Abstract : These results suggest that aerobic capacity and metabolic status influence sensory sensitivity and aspects of inflammation in peripheral tissues that could lead to poor responses to tissue damage and painful stimuli. The LCR and HCR rats should prove useful as models to assess how the metabolic status impacts pain.